Sustainable public procurement, does the state induce sustainability with its purchasing power? - Tardan, Jorge Luiz P. (2020)
The purpose of this document is to provide a snapshot of the influence of government purchasing power on the behavior of the market of good suppliers. In this case, the analyzed influence was the environmental sustainability promoted through public procurement. In a longitudinal study conducted on the acquisition processes of the Brazilian federal public administration, classified as sustainable, of 2016 and 2017, the effectiveness of these processes with respect to the sustainability promoted was evaluated. The evaluation was carried out by verifying the quantity of items related to purchasing in each process that could have environmental sustainability guidelines in their specifications and, those that really had such guidelines. The result was called effectiveness of environmental sustainability in the specification of the items, such percentages are shown in Tables 2 and 3. The conclusion lists possible restrictions on the show results, as well as deeper problems that could contribute to changes in the methodology of government procurement, Brazilian federal government and the culture that guides public procurement processes in Brazil. Problems that are considered crucial for better results.